The Fall of Afghanistan: Can the Refugee Protection Regime Handle the New Refugee Wave? - Qazi Zada, Sebghatullah; Nasrullah, Nasrullah; Irrynta, Dwilani; Qazi Zada, Mohd Ziaolhaq (Universitas Muhammadiyah Yogyakarta, 2024)
The Taliban takeover of Afghanistan on August 15, 2021, triggered a significant refugee crisis. By mid-2022, 2.8 million Afghan refugees were registered internationally, primarily in Pakistan and Iran, and by 2023, 4.3 million Afghans were internally displaced. Many at-risk Afghans were left behind as US-led forces withdrew. Despite resettlement efforts, many threatened by the Taliban remain excluded, as the Taliban targets former military, NGO workers, and Afghan government officials. Daily migration to Iran and Pakistan surged, with many seeking refuge through Iran to Turkey and Europe. This paper examines whether the current refugee protection mechanism can manage this influx. Using a normative legal research method, it analyzes secondary data from books, journals, reports, and documents, providing historical context on Afghan politics and displacement. It critically evaluates the international refugee protection regime, identifying gaps and shortcomings, particularly the lack of a binding responsibility-sharing mechanism. This has resulted in poorer nations hosting a disproportionate number of refugees, necessitating a commitment from the international community to address this inequity. The paper concludes with policy recommendations to improve the global response to the Afghan refugee crisis, emphasizing the need for equitable responsibility-sharing to enhance protection for Afghan refugees.